Anticoagulants utilization in eight hospitals within the Luzhou region from 2019 to 2023. - Wei Luo; Yan Li; Jiali Yang; Yang Liu; Yue Shi; Hongli Luo (PLoS ONE)
Background With the increasing utilization of anticoagulants, the selection of appropriate anticoagulants has emerged as a significant quandary. The objective of this study was to evaluate recent trend in the utilization and expenditure of anticoagulants within a specific region, aiming to provide valuable insights into the optimal choice of anticoagulants across other healthcare facilities. Methods The utilization of anticoagulants was retrospectively analyzed. The data on anticoagulant utilizations in tertiary-care hospitals within a district were collected from January 2019 to December 2023. The expenditure, defined daily doses (DDDs), and defined daily cost (DDC) were calculated. The trends in the utilization and expenditure of anticoagulants were examined using linear regression analysis. Results From 2019 to 2023, the DDDs of rivaroxaban demonstrated a significant annual increase in most hospitals (p < 0.05). Only a few hospitals exhibited a gradual rise in the consumption of low molecular weight heparin (LMWH) over the same period (p < 0.05). The trend of heparin sodium and warfarin varied across different hospitals. The implementation of the centralized procurement policy, however, resulted in a decline in the consumption of rivaroxaban and LMWH in 2021 and 2022 respectively. The DDC value of rivaroxaban experienced a substantial decrease over the past five years (p = 0.020), declining from 55.20 Chinese Yuan (CNY) in 2019 to 4.28 CNY in 2023. Conversely, there was a slight increase noted in the DDC of heparin sodium during this time frame (p = 0.042). Conclusion Over the past five years (2019-2023), there has been an increase in the utilization of rivaroxaban and LMWH. However, their expenditure has decreased. In addition, the utilization and expenditure of warfarin and heparin sodium remained relatively stable. The application prospects of rivaroxaban and LMWH are promising.